Tissue Engineering Strategies for Peripheral Nerve Regeneration - Yin Li (Frontiers Media S.A., 2021)
A peripheral nerve injury (PNI) has severe and profound effects on the life of a patient. The therapeutic approach remains one of the most challenging clinical problems. In recent years, many constructive nerve regeneration schemes are proposed at home and abroad. Nerve tissue engineering plays an important role. It develops an ideal nerve substitute called artificial nerve. Given the complexity of nerve regeneration, this review summarizes the pathophysiology and tissue-engineered repairing strategies of the PNI. Moreover, we discussed the scaffolds and seed cells for neural tissue engineering. Furthermore, we have emphasized the role of 3D printing in tissue engineering.